Identifying potential artificial groundwater recharge sites in Metro Manila for stormwater disposal using GIS techniques - Blancada, Stephen Russel S.
Due to high urbanization of Metro Manila, extreme flooding and groundwater depletion is already evident. The proposed engineering technology is the artificial groundwater recharge, which purposefully puts excessive stormwater back into the aquifer. However conventional hydrogeological tests would be impractical over large areas. Remote sensing and geographical information system (GIS) techniques are useful tools in searching for compatible sites of artificial groundwater recharge considering different factors that govern. To identify potential artificial groundwater recharge sites in Metro Manila, the Boolean satisfactory levels of the parameters were first set to the following values: lower than 8% slope, alluvial geology, non-built-up land cover, depth to groundwater level greater than 20 meters, electrical conductivity lower than 1500 µSiem, aquifer transmissivity higher than 100m²/day and low to high flood susceptibility. Raster maps of these layers were transformed into Boolean maps and the artificial groundwater recharge suitability map was produced by superimposing these Boolean map layers. Through the help of the suitability map, seven specific potential sites for artificial groundwater recharge in Metro Manila were identified: three in Marikina and one each on Manila, Quezon City, Muntinlupa and Makati